The Efficacy of Intravitreal Conbercept for Chronic Central Serous Chorioretinopathy. (7th May 2019) - Mao, Jianbo; Zhang, Caiyun; Liu, Chenyi; Shen, Lijun; Lao, Jimeng; Shao, Yirun; Chen, Yiqi; Tao, Jiwei
Abstract : Purpose . To evaluate the efficacy and safety of conbercept for patients with chronic central serous chorioretinopathy (CSC). Methods . A retrospective clinical study. Thirty-one patients (35 eyes) with chronic CSC were given intravitreal injections of conbercept and followed up for at least 6 months. Observed indicators included best-corrected visual acuity (BCVA), central macular thickness (CMT), and resolution of subretinal fluid (SRF). Serial changes in BCVA and CMT were analyzed by using repeated measures analysis of variance. Results . During the 6-month follow-up, the mean number of injections required and performed was 1.77 ± 0.60. The logMAR BCVA was 0.48 ± 0.26 at the baseline, 0.34 ± 0.26, 0.30 ± 0.26, 0.27 ± 0.26, 0.24 ± 0.26, and 0.23 ± 0.26 at 2-week and 1-, 2-, 3-, and 6-month follow-ups, respectively ( F  = 27.173, P < 0.05 ). CMT was 313.74 ± 144.51  μ m at the baseline and decreased to 263.49 ± 120.44  μ m, 225.91 ± 91.98  μ m, 195.77 ± 66.69  μ m, 189.74 ± 65.41  μ m, and 199.49 ± 81.50  μ m at 2-week and 1-, 2-, 3-, and 6-month follow-ups, respectively ( F  = 18.093, P < 0.05 ). Full resolution of SRF was achieved in 8 (22.9%) eyes at 1 month, 16 (45.7%) eyes at 2 months, 22 (62.9%) eyes at 3 months, and 27 (77.1%) eyes at 6 months after the initial treatment of anti-VEGF injection. No severe adverse event was noted relevant to the therapy. Conclusions . Intravitreal injection of conbercept may effectively reduce the CMT and improve the BCVA in chronic CSC in a short term of 6 months.